Modification, Performance and Adaptation of Manually Operated Transplanting and Seeding Machines for Lowland Paddy - Islam, Md. Syedul (1998)
An experiment was conducted for improvement of the 6-row manually operated rice transplanter designed by Intemational Rice Research Institute ( IRRI) to be adapted in the rice producing countries. After modification, a 5-row prototype was developed at the Bangladesh Rice Research Institute (BRRI), and both transplanters were evaluated and compared with hand transplanting method. A supplementary experiment was conducted to identify the optimum quality of the seedling mat for an improvement of the transplanter performance. Another experiment was conducted to improve the performance of IRRI designed drum seeder for lowland paddy. The machine was evaluated and compared with the hand seeding method. The wooden skid of the IRRI transplanter was replaced by a skid made of G.I. sheet in BRRI transplanter which made it durable, light weight and incurred less sliding resistance. As a result, the dragging force for modified transplanter was reduced by 30% compared to the previous prototype. The circular configuration of the picker finger of IRRI transplanter was modified to a semi-circular one which improved its cutting action. The effective field capacities of IRRI transplanter, BRRI transplanter and the hand transplanting methods were 0.0155 ha/hr, 0.0191 ha/hr and 0.0023 ha/hr respectively. As a result, a 20% increase in working capacity was achieved with BRRI transplanter over IRRI transplanter. The field efficiencies of I RRI and BRRI transplanters were 76.83% and 78.90% which were similar, but that of hand transplanting method was 91.40% which was significantly higher than those of machine transplanting. Seedling per hill in machine transplanting was significantly higher than hand transplanting method due to excessive seedling density in the nursery. The missing hills in IRRI and BRRI transplanters were 3.81% and 3.66% respectively which were mostly identical but in case of hand transplanting method, the missing hill was nil. The rice yields from the fields planted by IRRI, BRRI and hand transplanting methods were not significantly different at 5% level.